2018
DOI: 10.1021/acsami.8b09185
|View full text |Cite
|
Sign up to set email alerts
|

Polyhedral Oligomeric Silsesquioxane (POSS)-Based Cationic Conjugated Oligoelectrolyte/Porphyrin for Efficient Energy Transfer and Multiamplified Antimicrobial Activity

Abstract: Cationic quaternary ammonium (QA) groups and reactive oxygen species as two main approaches for antibacterial study have been intensively studied. Herein, we report a multifunctional antimicrobial agent (porphyrin-POSS-OPVE, PPO), which combines bacterial membrane intercalation, high density of local QA groups, efficient energy transfer, significantly reduced aggregation, and high water solubility into one single molecule. The light-harvesting PPO contains multiple donor-absorbing arms (oligo( p-phenylenevinyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 44 publications
3
46
1
Order By: Relevance
“…Chen et al reported an energy transfer system based on a cationic conjugated oligoelectrolyte donor and porphyrin acceptor for use in photodynamic antimicrobial chemotherapy ( Figure ). [ 88 ] In this system, each porphyrin unit was functionalized with four POSS cages, which contained seven additional (oligo( p ‐phenylenevinylene) (OPVE) electrolyte donor groups, creating a large macromolecule with a porphyrin acceptor center and a POSS star‐like structure. In this example, the POSS was used to reduce the aggregation of the porphyrin sites but also to act as a highly functionalizable bridging group, which increased the local concentration of oligoelectrolyte groups, thus enhancing the solubility.…”
Section: Applications Of Poss As Photoluminescent Materialsmentioning
confidence: 99%
“…Chen et al reported an energy transfer system based on a cationic conjugated oligoelectrolyte donor and porphyrin acceptor for use in photodynamic antimicrobial chemotherapy ( Figure ). [ 88 ] In this system, each porphyrin unit was functionalized with four POSS cages, which contained seven additional (oligo( p ‐phenylenevinylene) (OPVE) electrolyte donor groups, creating a large macromolecule with a porphyrin acceptor center and a POSS star‐like structure. In this example, the POSS was used to reduce the aggregation of the porphyrin sites but also to act as a highly functionalizable bridging group, which increased the local concentration of oligoelectrolyte groups, thus enhancing the solubility.…”
Section: Applications Of Poss As Photoluminescent Materialsmentioning
confidence: 99%
“…[159,174] Recently, Wang, Bao and co-workers designed a POSS-COE based porphyrin for efficient energy transfer from COE to porphyrin and achieved amplified antimicrobial activity. [175] However, the absorption peaks of those OPEs are around 326 nm to 355 nm. [176] Longer wavelength absorption would be desirable to achieve lower toxicity to mammalian cells and deeper tissue penetration.…”
Section: Pdt With External Light Sourcementioning
confidence: 99%
“…Among these, the incorporation of polyhedral oligomeric silsesquioxane (POSS) has attracted attention because of its unique frame structure and the resulting chemical and physical properties, including high thermal properties [18][19][20], lower crystallinity [21], mechanical properties [22], oxidation resistance, and very good dielectric properties [23,24]. Hence, it has been widely used in preparing polymer hybrids and polymer composites in many areas, including optics [25], electronics, ionic liquids [26], mechanics [27], energy [28], environment [29], biology [30], smart coatings [31,32], fuel [33], solar cells [34], catalysts [35,36], sensors [37][38][39], light-emitting devices [40], and medicine [41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%